Tax questions and answers - Fisher, R. K.; Hodgson, Helen M. (Thomson Reuters (Professional) Australia Limited, 2010)
Presents over 500 questions across the breadth of topics covered in undergraduate taxation. Used throughout the course of study it will assist in evaluating progress and identifying areas to focus on. Rodney Fisher, Faculty of LAW, UTS and Helen Hodgson, ATAX, Uni of New South Wales